Human Resource Management Practices in Hospitality Sector - Mohanty, Sasmita; B Pradhan, Bibhuti (International Journal of Psychosocial Rehabilitation, 2025)
Human Resource Management, an essential part of a company, also guarantees that the working partnership between workers and an organisation is effective by recognizing and meeting the needs of workers beginning from recruiting and progressing throughout their careers. This paper analyses the activities of human resources in hotels in the rugged state of Uttarakhand, India in the Himalayas. India's particular geographic position poses barriers to human resources that are special to this popular tourist destination. Reports from this survey shows that workers are happy with their remuneration packages but not with quality of employment, and the turnover rate of workers is comparatively high. Hoteliers do not often provide adequate training to develop the operational skills of employees. Recruitment is mainly through internal referrals that lead to high inbreeding and other human resource problems that follow.